A new condition for asymptotic consensus over switching graphs. (November 2018) - Chowdhury, Nilanjan Roy; Sukumar, Srikant; Chatterjee, Debasish
Abstract: We investigate asymptotic consensus of linear systems under a class of switching communication graphs. We significantly relax several reciprocity and connectivity assumptions prevalent in the consensus literature by employing switched-systems techniques to establish consensus. Our results rely solely on asymptotic properties of the switching communication graphs in contrast to classical average dwell-time conditions. A bound on the uniform rate of convergence to consensus is also established as part of this work.